Formation of consumer loyalty in the field of digital ecosystem products - E. I. Khalif; M. V. Rossinskaya (Путеводитель предпринимателя, 2024)
The article is devoted to studying the importance of increasing customer loyalty for successful business development in the digital era. The author identifies brand equity, customer trust and satisfaction as key factors influencing the level of customer loyalty. The article identifies the complexities of the modern market and the need to use digital tools to form and maintain consumer loyalty.The study aims to identify methods for building customer loyalty, including analyzing the importance of various factors, market segmentation and the use of digital technologies. The results of the study will be useful for companies aimed at strengthening their base of loyal customers.It is worth not only satisfying the needs of customers, but also building emotional connections with them, taking into account their individual preferences. The author draws attention to the importance of service quality, brand reputation, pricing and personalization in creating and maintaining customer loyalty.The study also highlights the importance of moving from product loyalty to brand loyalty to increase customer retention and ensure sustainable business growth. Particular attention is paid to the emotional connection with clients and the importance of quality of service in establishing long–term relationships.